A268 IATROGENIC ESOPHAGEAL STRICUTRE RESULTING FROM CIRCUMFERENTIAL SPREAD OF INJECTED CYANOACRYLATE GLUE. (15th March 2019) - Yang, D Y; Homenauth, R; Sandha, G S
Abstract: Background: Cyanoacrylate glue has been widely used in the endoscopic treatment of esophageal and gastric varices. The monomeric substance polymerizes upon contact with water or blood, achieving hemostasis by physically occluding bleeding vessels and initiating local thrombosis. While its efficacy has been demonstrated in multiple studies, there are also many reported complications, with the most significant being distal embolization, extrusion into the lumen, and local ischemia with tissue damage. However, there are no reported cases of circumferential spread of glue causing esophageal strictures. Aims: This report aims to present two cases of a previously unreported complication of esophageal glue injection. Methods: Retrospective review of two patients. Results: Case 1 involves the injection of 6 mL of cyanoacrylate glue into the distal esophagus of a 49-year-old male to stop bleeding from a submucosal tract formed by traumatic nasogastric tube insertion. The patient had no known underlying gastro-esophageal pathology. He developed solid and liquid food dysphagia 4 weeks after the procedure. Repeat upper endoscopy identified a stricture at the level of previous glue injection. A barium swallow and CT chest (Figure 1A and 1B) confirmed narrowing in the distal esophagus and illustrated the presence of mural-based hyper-attenuating material. The endoscopic and radiographic findings were consistent with the submucosal, circumferential spread of injected glue, leading to stricture formation at the site of injection. The stricture was treated with esophageal stenting with good effect.Case 2 involves a 58-year-old male who had esophageal glue injection for variceal bleeding after failed banding. He developed mild solid food dysphagia a few days after glue injection. Repeat upper endoscopy done 10 weeks later for recurrent upper GI bleed found a 2 cm x 3 cm ulceration at the glue injection site with the ulcer base having the appearance of solidified glue. CT scan identified radiopaque material encircling the entire circumference of the esophagus. Interestingly, there was no obvious stricture seen on endoscopy. The patient's symptom of dysphagia can be explained by the impairment of esophageal distention during the passage of food, leading to a relative narrowing of the esophagus. Given the presence of ulceration and his mild symptomology, no active intervention took place. Conclusions: These two cases illustrate the formation of esophageal stricture by the circumferential spread of cyanoacrylate glue. A comprehensive literature search has failed to find reports of similar nature. The reporting of this previously unknown complication will hopefully prevent such occurrences in future. Funding Agencies: None